CATCH ESTIMATION AND SIZE DISTRIBUTION OF BILLFISHES LANDED IN PORT OF BENOA, BALI - Bram Setyadji; Jumariadi Jumariadi; Budi Nugraha (Indonesian Fisheries Research Journal, 2012)
Billfishes are generally considered as by-product in tuna long line fisheries that have high economic value in the market. By far, the information about Indian Ocean billfish biology and fisheries especially in Indonesia is very limited. This research aimed to elucidate the estimation of production and size distribution of billfishes landed in port of Benoa during 2010 (February – December) through daily observation at the processing plants. The result showed that the landings dominated by Swordfish (Xiphias gladius) 54.9%, Blue marlin (Makaira mazara) 17.8% and Black marlin (Makaira indica) 13.0% respectively, followed by small amount of striped marlin (Tetrapturus audax), sailfish (Istiophorus platypterus), and shortbil spearfish (Tetrapturus Angustirostris). Generally the individual size of billfishes range between 68 and 206 cm (PFL), and showing negative allometric pattern except on swordfish that was isometric. Most of the billfish landed haven’t reached their first sexual maturity.